Applying invariant eigen-operator method to deriving normal coordinates of general classical Hamiltonian - 范洪义 陈俊华 袁洪春 (Chinese physics B, 2010)
For classical Hamiltonian with general form H = 1/2∑ijMijpipj＋1/2∑ijLijqiqj we find a new convenient way to obtain its normal coordinates, namely, let H be quantised and then employ the invariant eigen-operator （IEO） method （Fan et al. 2004 Phys. Lett. A 321 75） to derive them. The general matrix equation, which relies on M and L, for obtaining the normal coordinates of H is derived.